Strain engineering induced interfacial self-assembly and intrinsic exchange bias in a manganite perovskite film - Cui, B.; Song, C.; Wang, G. Y.; Mao, H. J.; Zeng, F.; Pan, F. (Scientific reports, 2013)
The control of complex oxide heterostructures at atomic level generates a rich spectrum of exotic properties and unexpected states at the interface between two separately prepared materials. The frustration of magnetization and conductivity of manganite perovskite at surface/interface which is inimical to their device applications, could also flourish in tailored functionalities in return. Here we prove that the exchange bias (EB) effect can unexpectedly emerge in a (La,Sr)MnO 3 (LSMO) “single” film when large compressive stress imposed through a lattice mismatched substrate. The intrinsic EB behavior is directly demonstrated to be originating from the exchange coupling between ferromagnetic LSMO and an unprecedented LaSrMnO 4 -based spin glass, formed under a large interfacial strain and subsequent self-assembly. The present results not only provide a strategy for producing a new class of delicately functional interface by strain engineering, but also shed promising light on fabricating the EB part of spintronic devices in a single step.